Prospective study of maturation and injury in elite handball academy. Could 'maturational status' be a risk factor for injury incidence in different handball team categories? - Mauricio Mónaco; Fernando Sanz Lopez; José A. Gutiérrez Rincón; J.Bruno Montoro Ronsano; Lourdes Ibañez Toda; Gil Rodas (Elsevier, 2024)
The objective of this study is to describe the relationship between injury incidence (IL) and maturity in male elite handball's player (HbP). Prospective study during two seasons, evaluating the sports injuries, maturity status and exposure time in hours in 133 young handball's players, under the UEFA methodology model for epidemiological studies. We discuss the maturity stage with different parameters, the Tanner's stage, puberty stages, peak high velocity, testicular volume, and the bone age. Finally, 190 injuries for a total of 34.222 h of exposure were registered.The average total Injury Incidence (IIn) by categories was 5,6 injury/1000 h of exposure. Injury Incidence during competition: 21,8 injuries/1000 hs and in training: 3,1 injuries/1000 hs without statistically significant between IIn, chronological age and different maturity stage by ANOVA.The multivariate statistical analysis registers tendency associations between IIn in competition for category (P = 0,07), and the IIn in training for Tanner stage (P = 0,091) and puberty (P = 0,021).In conclusion: there is not a significant difference in total IIn by ages categories in handball players but there is statistically significance tendency respect to some maturity parameters under a multivariate analysis. This last result must be considered when planning training seasons and strategies for injury prevention in the context of the formative handball.